Dynamic Mechanical Response and Dissipated Energy Analysis of Sandstone under Freeze-Thaw Cycles. (10th November 2021) - Man, Ke; Liu, Zongxu; Song, Zhifei; Liu, Xiaoli
Abstract : Based on the sandstone from the slope of Baorixile open-pit mining area in Hulunbuir City, Inner Mongolia, the dynamic uniaxial compression test of sandstone with different freeze-thaw cycles has been carried out by Split Hopkinson Pressure Bar test (SHPB). The test results show that the crushing degree of sandstone becomes serious with the freeze-thaw cycle times and strain rate increases. The dynamic compressive strength increases with the raise of strain rate under the same freeze-thaw cycles, while it reduces with the increases of freeze-thaw cycles at the same strain rate. It is found that the 10 freeze-thaw cycles are an obvious inflection point. When it is less than 10 cycles, the dynamic compressive strength of sandstone specimens decreases rapidly, it is more than 10 cycles, and the strength decreases gradually. This is due to that the evolution progress of pores in sandstone is more uniform after a certain number of freeze-thaw cycles. Meantime, the effect of freezing and thawing is mostly restrained by the pore evolution. On the other hand, the dissipated energy required for sandstone failure grows up with the increase of the number of freeze-thaw cycles. It shows that more energy is needed for the engender of pores and fractures in sandstone caused by freeze-thaw cycle. This led to the deterioration of sandstone structural stability and the decrease of dynamic mechanical properties.